2015
DOI: 10.1111/jdi.12401
|View full text |Cite
|
Sign up to set email alerts
|

Euglycemic diabetic ketoacidosis induced by SGLT2 inhibitors: possible mechanism and contributing factors

Abstract: It is possible that SGLT2 inhibitors trigger euglycemic diabetic ketoacidosis in some patients. Possible mechanism of euglycemic DKA induced by SGLT2 inhibitors is illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
251
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(264 citation statements)
references
References 6 publications
4
251
2
7
Order By: Relevance
“…Currently, SGLT2 inhibitors including canagliflozin, dapagliflozin, and empagliflozin were approved to use in T2DM recently, but not in T1DM. Pharmacologically, the anti-hyperglycemic mechanism of SGLT2 inhibitors was through decreasing glucose reabsorption in proximal renal tubules, subsequently leading to decreased insulin secretion, vicariously increased glucagon levels, and then potentially could exaggerate the process of ketogenesis [4]. As a result, the misuse of SGLT2 inhibitors in autoimmune diabetes can pose a high risk to develop euDKA, as the present case illustrated.…”
Section: Case Reportmentioning
confidence: 83%
See 1 more Smart Citation
“…Currently, SGLT2 inhibitors including canagliflozin, dapagliflozin, and empagliflozin were approved to use in T2DM recently, but not in T1DM. Pharmacologically, the anti-hyperglycemic mechanism of SGLT2 inhibitors was through decreasing glucose reabsorption in proximal renal tubules, subsequently leading to decreased insulin secretion, vicariously increased glucagon levels, and then potentially could exaggerate the process of ketogenesis [4]. As a result, the misuse of SGLT2 inhibitors in autoimmune diabetes can pose a high risk to develop euDKA, as the present case illustrated.…”
Section: Case Reportmentioning
confidence: 83%
“…Sodium-glucose cotransporter 2 (SGLT2) inhibitors are the newly-approved oral antihyperglycemic drug (OAD) in T2DM which increase renal glucose excretion to control hyperglycemia. On the other hand, they are associated with increased plasma glucagon level and ketogenesis, then precipitates the development of euglycemic DKA (euDKA) in patients with T1DM [4]. Here we present an overweight girl treated with multiple OADs under the presumed diagnosis of T2DM due to her habitus and family history of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…SGLT2 inhibitors work by blocking glucose reabsorption in the proximal renal tubule [2]. Evidence also indicates that SGLT2 inhibitors directly act on pancreatic alpha-cells to stimulate glucagon secretion causing increased ketone body production [3], and that SGLT2 inhibitors decrease renal clearance of ketone bodies [4].…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis results are shown in Fig Previous trials reported increased DKA cases with the use of SGLT2 inhibitors, especially when they were used off-label in patients with type 1 diabetes (2,3). Some plausible mechanisms are already proposed by which SGLT2 inhibitors might trigger DKA (3,15). Given the current evidence from RCT data, we found that SGLT2 inhibitors were not significantly associated with an increased risk of DKA among patients with T2D.…”
mentioning
confidence: 99%
“…However, the overall health benefits of these drugs needed to outweigh their possible side effects. Recently, cumulative evidence suggests that SGLT2 inhibitors may lead to diabetic ketoacidosis (DKA), which is a serious acute complication of diabetes (2,3). In May 2015, the U.S. Food and Drug Administration issued an updated drug safety communication warning about SGLT2 inhibitors potentially increasing the risk of DKA (4).…”
mentioning
confidence: 99%